Studi Kritis Terhadap Pendidikan Sekuler - Muhammad Nur Kadir; Radjiman Ismail; Natsir Machmud (Peneliti.net, 2023)
Education is a basic need for every human being. The purpose of education is to shape humans so that they can adapt in their lives, by developing the various potentials that exist within them. In this educational process, various views are faced, including understanding related to secular ideas in the world of education. In this paper the author will discuss and criticize about secular education. Education in the current era is experiencing various challenges from secularism to applying the noble values ​​of religious teachings in the social life of Muslims who are very pragmatic, even tend to be opportunistic. Secular ideas in contemporary life are presented and packaged in such a beautiful way through globalization and modernization, which are in line with the development of Western civilization. Secularism is an ideology that tries to eliminate religious values ​​originating from revelation in world life, or separates religious life from the world which is actually different from the goal of education, namely to form pious human beings.